Fecal microbiota transplantation for recurrent Clostridium difficile infection in a patient with ulcerative colitis - Nanki, Kosaku (Intest Res, 2018)
Fecal microbiota transplantation (FMT) has been reported as a safe and effective therapy in patients with refractory and recurrent Clostridium difficile infection (CDI). FMT has also been reported as a promising therapy in patients with ulcerative colitis (UC). Both, CDI and UC, are believed to be caused by dysbiosis, such as altered compositions or decreased diversity of the intestinal microbiota. This report describes a patient with UC in remission with a second recurrent episode of CDI, who was treated with FMT. A single FMT performed via colonoscopy completely resolved the patient's diarrhea and eradicated C. difficile bacteriologically without any severe complications. Molecular biological analysis of the patient's fecal microbiota showed that FMT could dramatically change the altered composition of intestinal microbiota and restore its diversity. Despite the restoration of the intestinal microbiota, FMT could not prevent a relapse of UC in this patient. However, it improved the intestinal symptoms of CDI and could prevent further recurrences of CDI.